2010
DOI: 10.1371/journal.pgen.1001227
|View full text |Cite
|
Sign up to set email alerts
|

The DNA Damage Response Pathway Contributes to the Stability of Chromosome III Derivatives Lacking Efficient Replicators

Abstract: In eukaryotic chromosomes, DNA replication initiates at multiple origins. Large inter-origin gaps arise when several adjacent origins fail to fire. Little is known about how cells cope with this situation. We created a derivative of Saccharomyces cerevisiae chromosome III lacking all efficient origins, the 5ORIΔ-ΔR fragment, as a model for chromosomes with large inter-origin gaps. We used this construct in a modified synthetic genetic array screen to identify genes whose products facilitate replication of long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 94 publications
4
32
1
Order By: Relevance
“…3) lacking a portion of the right arm (referred to as Chr3ΔR, 170 kb) can be maintained in cells containing a normal Chr. 3 (Theis et al, 2007, 2010) (Figure 7A). One variant has 12 ARSs and the other has 7 ARSs, and are referred to as Chr3ΔR-12ARS and Chr3ΔR-7ARS, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) lacking a portion of the right arm (referred to as Chr3ΔR, 170 kb) can be maintained in cells containing a normal Chr. 3 (Theis et al, 2007, 2010) (Figure 7A). One variant has 12 ARSs and the other has 7 ARSs, and are referred to as Chr3ΔR-12ARS and Chr3ΔR-7ARS, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…One variant has 12 ARSs and the other has 7 ARSs, and are referred to as Chr3ΔR-12ARS and Chr3ΔR-7ARS, respectively. The extra five ARSs in the former are known to fire, and thus greatly reduce replicon sizes (Theis et al, 2007, 2010). Using PFGE coupled with Southern blot analysis, fully replicated Chr.…”
Section: Resultsmentioning
confidence: 99%
“…Supporting experimental evidence also shows that for a chromosome with a 160 kb origin-less telomeric region, the rate of loss is more than 20 times higher than in the same region within a chromosome body. 35 Yet, this effect appears to be smaller than theoretically predicted, which may imply that some additional mechanism exists to enhance telomeric replication. It still consistently confirms the thesis of origin distribution being determined by the risk of stall events as one of major factors.…”
mentioning
confidence: 80%
“…The chromosome with an origin-less region of approximately 160 kb (close to the calculated maximum gap) had a 3 times higher loss rate compared to the correct value. 35 This overall protection against fork stalling does not reflect dormancy or activity of origins, but rather the total number of licensed ROs.…”
mentioning
confidence: 99%
“…Large inter-origin distances should therefore be avoided, and in all 5 yeasts examined ( S. cerevisiae , S. pombe , Kluyveromyces lactis , Lachancea kluyveri and Lachancea waltii ) this is clearly the case. Indeed, previous work [75] had shown that deletion of five origins in S. cerevisiae , creating a large inter-origin distance of 160 kb (close to the expected value of the largest inter-origin distance if origins were randomly distributed), resulted in an increased chromosome loss rate exactly in line with the increased probability of double fork stalls [57]. In order to globally minimize large gaps and the probability of double fork stalls, it is also optimal to position replication origins at regularly spaced intervals across the genome.…”
Section: Origin Distributionmentioning
confidence: 96%